Children’s Play Based Disaster Mitigation at SDN 20 Gumarang, Agam District - Feri Novriadi; Risda Amini (International Conference on Elementary Education, 2023)
The purpose of this study is to describe earthquake disaster mitigation to increase students' understanding of earthquake disaster preparedness. The method used in this research is descriptive qualitative. Collection of data and information related to research is done by observation and test. The results show that earthquake disaster mitigation can be done through children's games such as poles or gobak sodor and picture games that are able to increase students' understanding and knowledge about the potential for natural disasters that exist in the school environment, namely, earthquakes. Out of a total of 30 students, 25 of them can understand the steps that can be taken when a natural disaster occurs. So that with this understanding, students can socialize or provide information to their friends in the school environment and at home.